SVP-like MADS Box Genes Control Dormancy and Budbreak in Apple - Wu, Rongmei; Tomes, Sumathi; Karunairetnam, Sakuntala; Tustin, Stuart D.; Hellens, Roger P.; Allan, Andrew C.; Macknight, Richard C.; Varkonyi-Gasic, Erika (Frontiers in Plant Science, 2017)
The annual growth cycle of trees is the result of seasonal cues. The onset of winter triggers an endodormant state preventing bud growth and, once a chilling requirement is satisfied, these buds enter an ecodormant state and resume growing. MADS-box genes with similarity to Arabidopsis SHORT VEGETATIVE PHASE (SVP) (the SVP-like and DORMANCY ASSOCIATED MADS-BOX (DAM) genes) have been implicated in regulating flowering and growth-dormancy cycles in perennials. Here, we identified and characterised the role of three DAM-like (MdDAMs) and two SHORT VEGETATIVE PHASE-like (MdSVPs) genes from apple (Malus x domestica ‘Royal Gala’). The expression of MdDAMa and MdDAMc indicated they may play a role in triggering autumn growth cessation. In contrast, the expression of MdDAMb, MdSVPa and MdSVPb suggested a role in maintaining bud dormancy. Consistent with this, ectopic expression of MdDAMb and MdSVPa in ‘Royal Gala’ apple plants resulted in delayed budbreak and architecture change due to constrained lateral shoot outgrowth, but normal flower and fruit development. The association of MdSVPa and MdSVPb expression with floral bud development in the low fruiting ‘Off’ trees of a biennial bearing cultivar ‘Sciros’ suggested the SVP genes might also play a role in floral meristem identity.